PENGARUH ECONOMIC VALUE ADDED (EVA), TOTAL ASSETS TURNOVER (TATO), DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA BURSA EFEK INDONESIA (BEI) YANG TERCANTUM DALAM INDEKS LQ45 - Ratno, Ratno (Katalogis, 2019)
The research intends to examine and analyze simultaneous and partial impacts of Economic Value Added (EVA), Total Assets Turnover (TATO), and Return On Equity (ROE) on Stock Price in Indonesia Stock Exchange (BEI) Index LQ 45. Based on the result of panel data, it shows adjusted R-Square value of 0.947970, which means that 94.79% of independent variables that consist of Economic Value Added (EVA), Total Assets Turnover (TATO), and Return On Equity (ROE) are able to affect stock price. Based on the hypothesis test, it indicates that Economic Value Added (EVA), Total Assets Turnover (TATO), and Return On Equity (ROE) simultaneously have significant impacts on stock price with f-value of 78.73768 with significance value is 0.000000, smaller than Î± =0.05. Partially, Economic Value Added has significance and negative impact on stock price with t-value of -3.653833, and significance of p-value is 0.0006, smaller than Î± =0.05. Â Total Assets Turnover has no impact on stock price with t-value of -0.332988, and significance of p-value is 0.7406, higher than Î± =0.05. Return On Equity has significant and negative impact on stock price with t-value of -5.902786 and significance of p-value is 0.0000, smaller than Î± =0.05.